2019
DOI: 10.1007/s00403-019-01906-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and contact with healthcare systems among patients with psoriasis and psoriatic arthritis: results from the NORdic PAtient survey of Psoriasis and Psoriatic arthritis (NORPAPP)

Abstract: Psoriasis (skin psoriasis, PsO) is a chronic inflammatory condition. In about one-third of cases, the joints are affected (psoriatic arthritis, PsA). Both conditions, especially PsA, profoundly impact patients’ health-related quality of life (HRQoL). To describe the impact of psoriasis on HRQoL and patients’ contact with the healthcare system in Sweden, Denmark, and Norway, the NORdic PAtient survey of Psoriasis and Psoriatic arthritis (NORPAPP) asked 22,050 adults randomly selected in Sweden, Denmark and Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
0
26
1
2
Order By: Relevance
“…In our study, 33% of the PsA patients reported to be moderately anxious or depressed whereas only 5% reported to be extremely anxious or depressed. In a Nordic survey, 16.2% of the PsO and 34.9% of the PsA patients reported feelings of anxiety and depression [21]. In a recently published systematic review article of mental health in PsA including 24 studies, the authors concluded that anxiety and depression are highly prevalent among PsA patients [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 33% of the PsA patients reported to be moderately anxious or depressed whereas only 5% reported to be extremely anxious or depressed. In a Nordic survey, 16.2% of the PsO and 34.9% of the PsA patients reported feelings of anxiety and depression [21]. In a recently published systematic review article of mental health in PsA including 24 studies, the authors concluded that anxiety and depression are highly prevalent among PsA patients [43].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep impairment has been reported to be more severe in PsA patients than in PsO patients [ 19 , 20 ]. In a Nordic survey, sleep disturbances were reported by 16% of patients with PsO but by 45% of patients with PsA [ 21 ]. In our study, the prevalence of PsA patients reporting sleep disturbances was 38% (defined by ≥ 5 on a 0–10 NRS).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances, which in our study was independently associated with impaired HRQoL, have also by others been reported to be frequent in PsA patients. 24 25 In a Nordic survey study, as many as 44.5% of the PsA patients reported sleep disturbances. 24 Anxiety was also, in the recent published study by Baviere et al , found to be independently associated with impaired HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…24 25 In a Nordic survey study, as many as 44.5% of the PsA patients reported sleep disturbances. 24 Anxiety was also, in the recent published study by Baviere et al , found to be independently associated with impaired HRQoL. 26 The impact of depression and anxiety on HRQoL of life is significant as also shown in our PsA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety in PsA patients has an independent association with quality of life, thus accentuating the need for its proper screening and management [17]. Depression was found to have a profound effect on the health-related quality of life in patients with PsA in the Nordic Patient Survey of Psoriasis and Psoriatic Arthritis (NORPAPP) [18]. A large study from the UK described an increase in deaths attributable to suicide in patients with PsA, as compared to the general population [19].…”
Section: The Consequence Of Depression/anxiety In Patients With Psorimentioning
confidence: 99%